Possible role of annexin A1/FPR2 pathway in COX2/NLRP3 inflammasome regulation in alveolar bone cells of estrogen-deficient female rats with diabetes mellitus - Sasso, Gisela Rodrigues Da Silva; Cerri, Paulo Sérgio [UNESP]; Sasso-Cerri, Estela [UNESP]; Simões, Manuel Jesus; Gil, Cristiane Damas; Florencio-Silva, Rinaldo (Wiley, 2024)
Background: Annexin A1 (ANXA1) and the NOD-like receptor family pyrin domain-containing protein 3 (NLRP3) inflammasome play important roles in bone remodeling. However, expression profiles of these factors in bone cells under diabetes mellitus (DM) and estrogen-deficient conditions are poorly understood. This study investigated the immunoexpression of ANXA1 and its formyl peptide receptor 2 (FPR2), as well as NLRP3 inflammasome mediators, during remodeling of the alveolar process in diabetic and estrogen-deficient rats. Methods: Twenty adult female Wistar rats were divided into four groups (n = 5): Sham-operated (SHAM) and ovariectomized (OVX) rats received a vehicle solution, and SHAM and OVX rats were intraperitoneally administered 60 mg/kg/body weight (BW) of streptozotocin (STZ) to induce DM (SHAM-Di and OVX-Di groups). After 7 weeks, the rats were euthanized and their maxillae were fixed in phosphate-buffered 4% formaldehyde and embedded in paraffin. Sections were stained with hematoxylin/eosin (H&E) and picrosirius red or subjected to immunohistochemical detection of ANXA1, FPR2, NLRP3, interleukin-1β (IL-1β), and cyclooxygenase-2 (COX2). Results: Estrogen deficiency and DM were associated with deleterious effects in bone tissue, as evidenced by a lower number of osteocytes and higher number of empty lacunae in the SHAM-Di and OVX-Di groups compared to the nondiabetic groups. Both diabetic groups showed a smaller vascular area and weaker collagen fiber birefringence intensity in alveolar bone tissue. A significantly higher number of ANXA1/FPR2-positive osteoblasts, osteocytes, and osteoclasts was accompanied by a significantly higher number of these cells immunolabeled for COX2, NLRP3, and IL-1β in the diabetic and OVX groups, especially in both estrogen-deficient and diabetic rats. Conclusion: These results indicate a possible role for the ANXA1/FPR2 pathway as a fine-tuning/anti-inflammatory regulator to counterbalance exacerbated COX2/NLRP3/IL-1β activation in bone cells during bone remodeling under estrogen deficiency and DM.
Keywords: alveolar process; annexin A1; diabetes mellitus; inflammasome; ovariectomy